2000
DOI: 10.1089/027245700315743
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of a Novel Recombinant Single-Chain Variable Fragment Antibody Against Western Equine Encephalitis Virus

Abstract: A novel recombinant single-chain fragment variable (scFv) antibody against Western equine encephalitis virus (WEE) was constructed and characterized. Using antibody phage display technology, a scFv was generated from the WEE specific hybridoma, 10B5 E7E2. The scFv was fused to a human heavy chain IgG1 constant region (CH1-CH3) and contained an intact 6 His tag and enterokinase recognition site (RS10B5huFc). The RS10B5huFc antibody was expressed in E. coli and purified by affinity chromatography as a 70-kDa pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Colony count and restriction analysis were conducted for evaluating the volume and quality of MG7 recombinant antibody library. The large volume of MG7 recombinant antibody library (2×10 6 ) and high recombinant rate (72.7%) confirmed that MG 7 phage antibody library comprised sufficient repertoire of recombinant clones for further research. ELISA assay and SDS-PAGE showed that the soluble MG 7 ScFv had antigen-binding activity and was M r 31.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Colony count and restriction analysis were conducted for evaluating the volume and quality of MG7 recombinant antibody library. The large volume of MG7 recombinant antibody library (2×10 6 ) and high recombinant rate (72.7%) confirmed that MG 7 phage antibody library comprised sufficient repertoire of recombinant clones for further research. ELISA assay and SDS-PAGE showed that the soluble MG 7 ScFv had antigen-binding activity and was M r 31.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, the B lymphocyte isolated from PBMC of immunized animals with given antigen is an alternative material source [20] . Besides the B lymphocyte population from patients or immunized animals, many kinds of antibody-producing hybridomas are also suitable as a kind of material source for construction of the recombinant phage antibody library [6,19] . Owing to the unraveling of biological functions over many antigen recognized by antibody from hybridomas, hybridomas are more favorable as material source for construction of recombinant phage antibody library.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prophylactic or early (within 24 h) administration provided passive protection, but not sterilizing immunity (Wyckoff & Tesar, 1939). Some mouse monoclonal antibodies were shown some of these antibodies were shown to provide protection from infection following passive transfer of antibody (Long, et al, 2000;Long, et al, 2001). Mice were protected from challenge with WEE when injected with antibodies against E1 and E2 in passive transfer studies (Hunt & Roehrig, 1985;Yamamoto, 1986).…”
Section: Antibody Responsementioning
confidence: 99%
“…To our knowledge no anti-WEEV antibody fragments derived from any kind of library is published. However, scFvs were generated from the murine IgGs 11D2 (Das et al, 2004;Xu et al, 1999) and 10B5 E7E2 (Long et al, 2000) for diagnostic purposes. The authors of this review generated scFvs against WEEV by phage display using a macaque immune antibody gene library (Rülker et al in preparation), both for diagnosis and therapeutic purposes.…”
Section: Antibodies For Diagnostics and Therapy Of Encephalitis Virusmentioning
confidence: 99%